Determinants of the Use of E-Wallet for Transaction Payment among College Students - Alwan Sri Kustono; Ardhya Yudistira Adi Nanggala; Imam Mas’ud (Journal of Economics, Business, & Accountancy Ventura, 2020)
This study aims to determine the factors that influence behavioral intentions to use E-wallet. The factors tested include application quality, perceived usefulness, perceived ease of use, and attitude toward using. The population in this study is college students in Jember Regency, Indonesia. Data analysis is carried out using Variance-based Partial Least Square. The number of samples used is 180 college students as users of the e-wallet application. Six hypotheses are tested, and four hypotheses are successfully accepted. Perceived ease of use has a positive effect on perceived usefulness. Perceived usefulness has a positive effect on attitude toward using e-wallet applications. Attitude plays a vital role in behavioral intentions to use e-wallets. The quality of the e-wallet application does not affect the level of perceived usefulness. The perceived ease of use of the application has no direct effect on attitude. This study's results are beneficial for e-wallet providers to increase the level of the use of e-wallet.